1986
DOI: 10.1084/jem.164.4.1226
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical localization and amino acid sequences of crossreactive epitopes within the group A streptococcal M6 protein.

Abstract: M protein is a fibrous, predominantly a-helical, coiled-coil molecule extending from the cell surface of group A streptococci (1, 2). Through its ability to allow this organism to escape phagocytosis by the host's defenses, M protein acts as the primary virulence factor for these streptococci . Protection from streptococcal infection is due primarily to opsonization by type-specific antibodies directed against the M protein (3).Previously, serological crossreactions among purified M proteins of various serotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
73
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 24 publications
2
73
0
Order By: Relevance
“…The recognition of the C repeat region by a large number of T cell lines is in accordance with the fact that all M protein serotypes share a large region of homology in the C repeat region of the molecule (34,47,48). M protein serotypes M5 and M6 share homology within the B repeat region (49,50), which is the basis for the sharing of epitopes in the B repeat region of M5 and M6 proteins. Consequently, M6-proteinspecific T cell clones proliferated to B repeat peptides of M5 protein.…”
Section: Discussionmentioning
confidence: 74%
“…The recognition of the C repeat region by a large number of T cell lines is in accordance with the fact that all M protein serotypes share a large region of homology in the C repeat region of the molecule (34,47,48). M protein serotypes M5 and M6 share homology within the B repeat region (49,50), which is the basis for the sharing of epitopes in the B repeat region of M5 and M6 proteins. Consequently, M6-proteinspecific T cell clones proliferated to B repeat peptides of M5 protein.…”
Section: Discussionmentioning
confidence: 74%
“…Although normal clumping was observed for JRS4, no clumping was seen for JRS145 or JRS470, suggesting that, like the M Ϫ strain, the sagA mutant strain lacks surface M protein. This was confirmed by spotting whole cells onto nitrocellulose membranes and developing the membranes with MAb 10A11, which recognizes an epitope in the B repeat region of the M6 protein (24), and with DIG-labeled fibrinogen, which binds M protein (53,54) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…4A). Whole-cell protein extracts from both wild-type and mutant strains were separated by SDS-PAGE and probed first with MAb 10A11, which recognizes an epitope in the B repeat region of the M6 molecule (24). The multiple banding pattern characteristic of full-length M6 protein (between Ϸ50 and Ϸ66 kDa) was observed in the wholecell extracts of wild-type strain JRS4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since type specificity resides at the amino termini of M proteins (25,26) and antibodies to the CRR were not opsonic, despite their ability to fix complement on whole bacterial cells (28), it was believed that antibodies to CRR could not provide protection through the opsonic mechanism. A more recent study has revealed that antibodies raised against CRR-derived peptides are capable of eliciting opsonic antibodies (41).…”
Section: Discussionmentioning
confidence: 99%
“…It facilitates colonization of mucosal surfaces and enables the organism to escape host immune surveillance (22,24,27,30). Fischetti and colleagues have identified a region of the M protein that is repeated within the protein and conserved among many, if not all, serotypes (C-repeat region [CRR]) (25,26). Importantly, CRR-specific secretory immunoglobulin A (IgA) but not systemic IgG protects animals against streptococcal pharyngeal infections at the mucosal point of entry, as judged by a reduction in pharyngeal infection following nasal challenge (2,3,5,15,16).…”
mentioning
confidence: 99%